Drivers of capital inflow: Does global uncertainty matter? - Kazeem Abimbola Sanusi; Forget Mingiri Kapingura (Cogent Business & Management, 2022)
Determinants of international capital inflow differ from one country to another, and as such country-specific studies are important in assisting each economy to understand cutting-edge policies which can be implemented to attain and retain desired capital inflow. The purpose of the present empirical effort is to examine the determinants of international capital inflow into the South African economy with special focus on the role of global uncertainty. The study investigated the determinants of portfolio inflow, direct capital inflow and total inflow using time series quarterly data from 1960(Q1) to 2021(Q3). The study employed the Dynamic Conditional Correlation (DCC GARCH) to investigate time-varying correlation among the variables in the light of more current data and Bayesian Linear Regression Model given its ability to deal with the problem of volatility. The overall picture that emerges from the study is that global uncertainty does not significantly correlate or affect portfolio inflow; while on the other hand, it negatively correlates and impacts direct capital inflow and total inflow. The implication is that government and South African policymakers should pay a closer attention to measures to mitigate global uncertainties in attempt to increase direct capital investment flow.
Keywords: 650; BLR; Capital inflow; DCC; determinants; global uncertainty index